A sensitive method for the sulfur isotope analysis of dimethyl sulfide and dimethylsulfoniopropionate in seawater. (31st October 2013) - Said‐Ahmad, Ward; Amrani, Alon
Abstract : RATIONALE: Dimethyl sulfide (DMS) is the major volatile sulfur species emitted to the atmosphere from the oceans. The sulfur isotope ratio ( 34 S/ 32 S) of DMS may offer a way to calculate the contribution of marine DMS to global sulfur cycling. The S‐isotopic analysis of DMS is difficult due to its low concentrations in natural seawater and high chemical reactivity. Here we present a sensitive, precise and accurate method for determining the S‐isotopic composition of natural DMS and its precursor, dimethylsulfoniopropionate (DMSP), in seawater. METHODS: The method was based on a purge of DMS from aqueous solutions or natural seawater to a cryogenic trap and subsequent separation of DMS by gas chromatography. The separated DMS was then transferred from the gas chromatograph to a multicollector inductively coupled plasma mass spectrometer (GC/MC‐ICPMS system) for measurement of 34 S/ 32 S ratios. Correction for mass bias was accomplished using standard‐sample bracketing with peaks of SF6 as a reference gas. RESULTS: Results obtained from synthetic DMS and DMSP dissolved in artificial seawater show >98% recovery of DMS and very good precision (0.1 to 0.3‰), accuracy and linearity (0.2‰) for the 26–179 picomoles (pmol) of DMS or DMSP injected. The system was tested with natural seawater from Eilat (Red Sea, Israel) and similar precision and accuracy for both DMS and DMSP were obtained. The δ 34 S values of DMS and DMSP from Eilat seawater were 19.2 ± 0.2‰ and 19.7 ± 0.2‰, respectively. CONCLUSIONS: The coupling of a purge‐and‐trap system with a GC/MC‐ICPMS system was shown to be a sensitive, accurate and robust approach for the S‐isotope analysis of nanomolar (nM) concentrations of DMS and DMSP from aqueous solutions and natural seawater. Copyright © 2013 John Wiley & Sons, Ltd.